Alil-aromáticos como matéria prima renovável para produção de arilbutenoatos via metátese cruzada de olefinas - Artur Vicari Granato (2014)
In this work the cross-metathesis reactions of substrates of natural sources (estragole, methyl eugenol, safrole and eugenol) with methyl acrylate using dichloroethane and dimethyl carbonate as solvent were studied employing the catalysts: Hoveyda-Grubbs second generation [dichloro (3,4-dihidro-dimesitylimidazolyl-ilidene) 2- isopropoxihenylilideneruthenium (II)] and Grubbs second-generation [dichloro (2,5-dimesitylimidazolyl-dynilidene)(tricyclohexylphosphine) benzylideneruthenium (II)]. These reactions were carried out with the aim of increasing the structural complexity of natural olefins order to recovery of abundant renewable inputs in tropical countries such as Brazil. The cross-metathesis reactions of allyl aromatic compounds with acrylate esters may have low yields as they are subject to side reactions. Reactions were carried out employing the Hoveyda-Grubbs catalyst 2nd generation systems free of solvents and in the presence of solvents. We could observe that using dichloroethane as solvent reasonably increases the yield to the desired metathesis products. In dichloroethane as solvent with the use of a small amount of catalyst (about 0.5 mol%) in 4 hours of reaction at 80 ° C in a schlenk flask, a 80% yield of the desired product was obtained. With the aim of increasing the yield for the desired product, reactions were carried out under continuous flow of argon. By removing volatiles formed during the reaction such as ethylene, the equilibrium of the reaction is displaced towards the products, which provides a reasonable increase in the yield of the reaction to the desired metathesis products. An analogous study was carried out employed the 2nd generation Grubbs catalyst. For this catalyst, the reactions carried without solvent (with excess methyl acrylate) the cross-metathesis of these substrates results in low yield for desired products. Using dichloroethane as solvent, using small amount of the catalyst (0.5 mol%) for 4 hours of reaction at 80 ° C in a schlenk tube, yields up to 70% were obtained. The use of an argon-swept reactor further increased the yield to 80% of the main cross-metathesis product. The cross-metathesis reactions of allyl aromatic compounds with methyl acrylate was also evaluated employing dimethyl carbonate as greener solvent. By using this solvent good conversions were obtained, however the yield to the main cross-metathesis products was reduced due to a subsequent double bond isomerization. To prevent isomerization, 1,4-benzoquinone was used as an additive. Employing 2nd generation Hoveyda-Grubbs catalyst the addition of 5 mol% of 1,4-benzoquinone allowed in some cases an improvement of 20% in the yield for the main product of cross metathesis. Employing 2nd generation Grubbs catalyst, the addition of 5 mol% of 1,4-benzoquinone allowed in some cases an improvement of 35%% in the yield for the main product of cross metathesis.